Životní situace rodiny po neanticipované ztrátě dítěte se zaměřením na životní úkoly pozůstalých rodičů - Zdeňka Dohnalová (AntropoWebzin, 2010)
In her article, the author tries to find the answer to the following question: „What life tasks do the parents after an unanticipated loss of the child face?“ This study results from a qualitative research, which  explores the exprerience of the surviving mothers after unanticipated loss. The autor presents the two periods of adapting to the loss of a  child and specific needs of families after bereavement. The study results show that the way of mourning is very individual. The life tasks of surviving parents depend on the general situation of the family (including the way they lived before the tragic event).  The strategies of solving these problems vary as well. However, our research proved explicitly that parents after a sudden loss of the child need help, not only psychological but also practical. Nevertheless various institutions and the people around them do not often provide them wih the help they need.